Characterization of Faecal Enterococci from Wild Birds in Turkey and Its Importance in Antimicrobial Resistance - DIREN SIGIRCI, B; CELIK, B; HALAC, B; BASARAN KAHRAMAN, B; BAGCIGIL, AF; AK, S (Journal of the Hellenic Veterinary Medical Society, 2021)
This research aimed to investigate the diversity of faecal enterococci isolated from wild birds, to detecttheir antibiotic resistance patterns and to determine their distribution of genes related to vancomycin resistance. Additionally, to investigate their virulence factors that are important in the development of the disease. One hundred seven cloacal/rectal samples were inoculated onto Enterococcus Agar, and presumptive colonies were identified and confirmed by PCR. Multiplex PCR assays were used to screen vanA, vanB, vanC1 and vanC2/3. The virulence-related genes; ace, gelE, efa and agg were determined by PCR. Among the 103 enterococci, 62 E.faecalis, 23 E.faecium 3 E.gallinarum, 2 E.durans, 1 E.casseliflavus and 12 Enterococcus spp. were identified. Of the 103 enterococci, 26 were found to be resistant against to three or more antibiotics. The highest percentages were detected for chloramphenicol (52%), tetracycline (33%) and erythromycin (30%). Two E.gallinarum isolates were harboring three virulence factors, and one isolate was carrying a single virulence factor. There is no virulence factor in the E.casseliflavus isolate. Also, vanA and vanB genes were not found. Forty-two of 103 enterococci were harboring virulence factors, more frequently in E.faecalis. Forty-two enterococci carried efa A, 31 isolates carried gel E, and ace was found in 18 isolates. Virulence gene agg was not detected. When the results of the study were evaluated in general, multiple drug resistance was described as 25%. Considering the risk of polluting the water resources of wild animals, it is suggested that the continuity of this type of epidemiological study in wildlife animals is necessary. In conclusion, the wild birds may act as substantial reservoirs carrying antimicrobial resistance among enterococci and estimate the potential risk for man, pets and farm animals.